OVERVIEW OF PIRATED SOFTWARE ON CAMPUS: EDUCATORS' PERSPECTIVE - Basrul Abdul Majid; Hendri Ahmadian (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
This research was conducted in order to get an overview from the teaching staff on pirated software. The results acquired were an overview about pirated software, the use of pirated software, the price and willingness to switch to original software. In general, the perception of respondents stated that they knew about pirated software (66.67%), those who did not know (28.07%) and a small proportion were still in doubt (5.26%) regarding this matter. However, almost half of the respondents said that they did not know that the laptop used pirated software (49.12%) and those who knew about it are 21.05%. Small proportion of respondents (19.82%) are still in doubt whether their laptop uses pirated software or not. Respondents who agree (62.28%) original software is expensive, are willing to buy (72.81%) do not want to buy and are hesitant (20.18%). Respondents who disagreed (17.54%) original software was expensive, hesitant to obtain it legally (7.02%). The use of pirated software takes other people's rights (77.19%) and also violates the Copyright Law (79.82%) and disagrees (12.28%) on this. Respondents who were still in doubt were 10.53% and 7.89%. Respondents want to switch (72.81%), not willing (7.02%). The hesitation to move is 20.18%. Only a small proportion (27.19%) of respondents who do not know where to buy it, those who know (41.23%). Not sure where to get it (31.58%).